Crystallization: Nanoparticle Growth via Concentration Gradients Generated by Enzyme Nanopatterns (Adv. Funct. Mater. 24/2014). (June 2014) - de la Rica, Roberto; Bat, Erhan; Herpoldt, Karla L.; Xie, Hai‐nan; Bertazzo, Sergio; Maynard, Heather D.; Stevens, Molly M.
<x xml:space="preserve">Abstract</x> Top‐down e‐beam lithography is combined with bottom‐up bioinspired crystal growth by R. de la Rica, M. M. Stevens, and co‐workers to grow nanoparticle clusters of controlled dimensions at desired locations on a chip. On page 3692, the key enabling factor to recreate biomineralization conditions is the patterning of enzyme nanoreactors as lines separated by nanometric distances such that the gradient of crystallization precursors generated by the enzymes is affected by the nanoscale organization of biocatalysts. Image Credit: Miguel Spuch‐Calvar. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>